Experimental Investigation of Effect of Pore Diameter on Nucleate Boiling Heat Transfer in Reentrant Tunnel Structured Surfaces - Ispir, Ali Can; Karatas, Tugce; Dikec, Eren; Onbasioglu, Seyhan (American Society of Mechanical Engineers, 2017)
This paper focuses on experimental studies of boiling heat transfer on surfaces with reentrant tunnels and pores. Three structured surface which have same tunnel width and height but different pore diameter, have been developed for enhancement boiling heat transfer. The experimental studies were carried out for the structured surfaces using distilled water at atmospheric pressure. The narrow reentrant tunnels are parallel to each other and have 3 mm width, 4 mm height. A number of pores whose diameter 1.5 and 2.0 mm were machined on lateral surfaces of tunnels. The surfaces were termed according to their geometric specifications as 3.0W-30-30, 1.5D-3.0W-30-30, 2.0D-3.0W-30-30. D and W capitals represent pore diameter and tunnel width, respectively. 30-30 part of name shows the dimension of square surface. The tunnels were used to increase area of heat transfer and active nucleation sites of vapor bubbles. In addition, sufficient amount of liquid must be supplied and vapor bubbles should be released fast from the boiling surface before they merge on the surfaces under conditions especially with high heat fluxes. Therefore, it was considered that pore structures would help for fluid transition hence the bubble frequency will increase. Pool boiling experiments were held to determine the performance of surfaces in different range of heat fluxes. Besides, high-speed visualization studies were conducted with high speed camera to observe behavior of nucleation of vapor bubbles. Amongst different geometry sizes the surface which has 1.5 mm of pore diameter (1.5D-3.0W-30-30) demonstrated the best nucleate boiling performance at high heat fluxes. However, the pored ones without pores has higher augmentation than pored structures at low heat fluxes. Thus, it is concluded that pored structures caused active nucleation sites to decrease under low heat fluxes.